Hepatic expression of proteasome subunit alpha type‐6 is upregulated during viral hepatitis and putatively regulates the expression of ISG15 ubiquitin‐like modifier, a proviral host gene in hepatitis C virus infection. Issue 5 (1st February 2016) - Broering, R.; Trippler, M.; Werner, M.; Real, C. I.; Megger, D. A.; Bracht, T.; Schweinsberg, V.; Sitek, B.; Eisenacher, M.; Meyer, H. E.; Baba, H. A.; Weber, F.; et al.
Summary: The interferon‐stimulated gene 15 (ISG15) plays an important role in the pathogenesis of hepatitis C virus (HCV) infection. ISG15‐regulated proteins have previously been identified that putatively affect this proviral interaction. The present observational study aimed to elucidate the relation between ISG15 and these host factors during HCV infection. Transcriptomic and proteomic analyses were performed using liver samples of HCV‐infected ( n = 54) and uninfected ( n = 10) or HBV‐infected controls ( n = 23). Primary human hepatocytes (PHH) were treated with Toll‐like receptor ligands, interferons and kinase inhibitors. Expression of ISG15 and proteasome subunit alpha type‐6 ( PSMA6 ) was suppressed in subgenomic HCV replicon cell lines using specific siRNAs. Comparison of hepatic expression patterns revealed significantly increased signals for ISG15, IFIT1, HNRNPK and PSMA6 on the protein level as well as ISG15, IFIT1 and PSMA6 on the mRNA level in HCV‐infected patients. In contrast to interferon‐stimulated genes, PSMA6 expression occurred independent of HCV load and genotype. In PHH, the expression of ISG15 and PSMA6 was distinctly induced by poly(I:C), depending on IRF3 activation or PI3K/AKT signalling, respectively. Suppression of PSMA6 in HCV replicon cells led to significant induction of ISG15 expression, thus combined knock‐down of both genes abrogated the antiviral effect induced by the separate suppression of ISG15 . These data indicate that hepatic expression of PSMA6, which is upregulated during viral hepatitis, likely depends on TLR3 activation. PSMA6 affects the expression of immunoregulatory ISG15, a proviral factor in the pathogenesis of HCV infection. Therefore, the proteasome might be involved in the enigmatic interaction between ISG15 and HCV.